Vertical restrictive strabismus associated with proptosis: Similar clinical signs, different etiopathogenetic causes. A report of three patients. Issue 2 (March 2022) - Savino, Gustavo; Petrone, Gianluigi; Volpe, Giulio; Midena, Giulia; Grimaldi, Gabriela; Fiorentino, Vincenzo; Maceroni, Martina
Purpose: To report the different uncommon pathogenesis of three cases of severe vertical restrictive strabismus associated with progressive unilateral proptosis with similar clinical features. Methods: Case series of three patients who presented to the Orbit Outpatient Service of Policlinico Gemelli with a history of left progressive unilateral proptosis, slowly worsening vertical strabismus and the left eye fixed in downward position. A thorough hematologic work up was performed. All patients underwent complete abdomen ultrasonography, orbital contrast enhanced magnetic resonance imaging, forced duction test under general anesthesia, and orbital biopsy. Results: Patients were 30, 60, and 46 years old respectively. MRI showed left inferior rectus enlargement in two cases and superior rectus enlargement in one case, with contrast enhanced combined muscle belly and tendon enlargement in all cases. Patients underwent forced duction test, muscle weakening (in two cases), and muscle biopsy with histopathologic examination. The superior rectus appeared infiltrated by an undifferentiated high-grade pleomorphic sarcoma, whereas the two inferior recti were positive for idiopathic orbital inflammatory disease with fibrosis areas and neuromuscular choristoma, respectively. Conclusion: Although proptosis and acquired vertical restrictive strabismus are most commonly associated with thyroid associated orbitopathy (TAO), they can also be a manifestation of many other conditions and the differential diagnosis can be particularly challenging. The three reported cases presented indeed with similar clinical features but had three distinct underlying orbital etiologies, two of which were extremely uncommon.